Adaptable privacy protection scheme in JPEG images - Hongxin WEN; Fei HU; Nenghai YU (网络与信息安全学报)
The JPEG format is widely used for its high compression rate in image storage.Privacy protection schemes applied to JPEG images not only need to safeguard the content of the privacy region but also maintain the file size.Furthermore, the region of interest (ROI), which contains private information, often occupies only a portion of the entire JPEG image.Protecting only the ROI can help preserve the file size.In light of this, an adaptable privacy protection scheme for JPEG images was proposed.Privacy regions were identified using methods like face detection within the JPEG images.These regions were then modified using the block-based adaptable reversible modification algorithm presented in this study.Reconstruction information was embedded into the image through reversible data hiding.The application of reversible algorithms in the privacy protection process enabled authorized users to fully restore the protected area.By introducing variable parameters, this scheme allowed for the selection of appropriate parameters to meet different practical requirements and achieve optimal encryption results.Additionally, the complex scenario of multiple overlapping ROIs was discussed and resolved.Experimental evaluations were conducted to investigate the influence of parameters on performance, considering both peak signal-to-noise ratio (PSNR) and file size increment.The results demonstrate that the proposed scheme outperforms existing schemes in terms of privacy protection and file size when suitable parameters are employed.